If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n = 3(n + 12) Reorder the terms: 5n = 3(12 + n) 5n = (12 * 3 + n * 3) 5n = (36 + 3n) Solving 5n = 36 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 5n + -3n = 36 + 3n + -3n Combine like terms: 5n + -3n = 2n 2n = 36 + 3n + -3n Combine like terms: 3n + -3n = 0 2n = 36 + 0 2n = 36 Divide each side by '2'. n = 18 Simplifying n = 18
| z^2+(4+2i)z+3-3i=0 | | x-2/135 | | 8c-9=-129 | | y/1-y | | 7=In(x+9) | | 8x+y=11+7y | | 1y=8-3y | | 2(x+4)=2(10x+1) | | x^2-5kx+5k-1=0 | | 3x=0.10-x | | 5xt-2xt= | | z^4=4i | | 3p+2q=5 | | x/5=36/20 | | x/4-2/5 | | 3.67=log(x) | | 4d+3=d-6 | | 2m-6=m+2 | | x^2-x-1=2x+1 | | X^2+28x=16 | | 12-(5x+3)+7(x+1)=8-2x | | logx=-0.45 | | 60+-25x=35x+20 | | t^2-5t-5=0 | | 14y+y^2+48=0 | | 2=sinx | | y=2((sinx)) | | 70=-7(-2-2x-z) | | 2x^2-392=0 | | 1400+s=2100 | | 70=-7(-2-2x-28) | | 5x+4=10-3x |